Fyn‐mediated phosphorylation of Pyk2 promotes its activation and dissociation downstream of gonadotropin‐releasing hormone receptor. (11th February 2020) - Higa‐Nakamine, Sayomi; Okitsu‐Sakurayama, Shiho; Kina, Shinichiro; Yamamoto, Hideyuki
Abstract : The receptor for gonadotropin‐releasing hormone (GnRH) is highly expressed in hypothalamic GnRH neurons, as well as in anterior pituitary gonadotrophs. In our previous study, we found that stimulation of the GnRH receptor activated protein kinase D1 (PKD1), and PKD1 was involved in the Fyn‐mediated activation of proline‐rich tyrosine kinase 2 (Pyk2) in cultured GnRH neurons (GT1‐7 cells). In the present study, we examined the molecular mechanisms of Pyk2 activation and the interaction of Pyk2 and Fyn in GT1‐7 cells. Experiments with site‐directed mutants of Pyk2 indicated that tyrosine 402 (Tyr402) was phosphorylated both by autophosphorylation and by Fyn, whereas Tyr579 was phosphorylated mainly by Fyn. We found that dasatinib, a Src family inhibitor, enhanced the interaction of Pyk2 and Fyn. Experiments with site‐directed mutants of Pyk2 and Fyn indicated that dasatinib enhanced the binding of Pyk2 autophosphorylated at Tyr402 and the Src homology 2 domain in Fyn. Our present data may suggest that fully activated Pyk2 dissociates from Fyn after Fyn‐mediated phosphorylation of Pyk2 at sites other than Tyr402 and Tyr579. Abstract : Gonadotrophin‐releasing hormone (GnRH) stimulates the GnRH receptor, resulting in proline‐rich tyrosine kinase 2 (Pyk2) forming an oligomer. The Tyr402 of Pyk2 in the oligomerized form is autophosphorylated in trans, followed by the binding of Fyn to the phosphorylated Tyr402. The bound Fyn subsequently phosphorylates Tyr579/580, resulting in the full activation of Pyk2. Fully activated Pyk2 may become dissociated from the Pyk2–Fyn complex through Fyn‐mediated phosphorylation of certain tyrosyl residues in Pyk2.